(untitled) (Bulletin of Innovative Research, 2026)
The article examines extralinguistic means in the works of Anton Chekhov. It analyses the functioning of non-verbal components of the literary text — gestures, mimicry, pauses, intonation, material detail and spatial organization — as important tools for revealing characters’ psychological states. Typological groups of extralinguistic means are identified in the stories«Дама с собачкой», «Ионыч», «Человек в футляре» (“The Lady with the Dog,” “Ionich,” “The Man in a Case,” and in the plays “The Cherry Orchard” and “Three Sisters”). The role of subtext and artistic detail in shaping the author’s conception of personality is investigated.